Matrix Composition Effect on the Characteristics of Isopulegol Nanofibers Fabrication by Electrospinning Method - Hidayati, Arina; Cahyono, Edy (Universitas Negeri Semarang, 2021)
Isopulegol is a highly volatile compound. One method for preserving highly volatile compounds is electrospinning. One of the factors that influence electrospinning stability is matrix composition. In this study, isopulegol-PVA nanofiber with a variety of matrix compositions is made by electrospinning techniques to determine the effect of matrix composition on the characteristics of nanofiber and the comparison of isopulegol peak area on the best nanofiber. Making solutions according to predetermined composition. The solution was electrospinning by setting a 10 mL syringe which has a metal needle with 0.6 mm inner diameter. Electrospinning parameters are adjusted, such as the voltage is 18 kV and the distance of the needle tip to the collector is 10 cm. The results of nanofiber were analyzed using FTIR-ATR and SEM. Based on the research, the composition of PVA-maltodextrin-isopulegol (1:1) nanofiber is better than PVA-maltodextrin-isopulegol (1:2) nanofiber. The composition of PVA- Î² -cyclodextrin-isopulegol (1:2) nanofiber produces better fiber than PVA- Î²-cyclodextrin-isopulegol(1:1) nanofiber. The diameter of the resulting PVA nanofiber is 92,891 nm; PVA-maltodextrin-isopulegol (1:1) nanofiber is 94.02 nm; and the PVA- Î² -cyclodextrin-isopulegol (1:2) nanofiber is 100,242 nm. The results of the comparison of isopulegol peak area from the best isopulegol nanofiber (PVA- Î² -cyclodextrin-isopulegol (1:2)) are unstable